The Pharmacoeconomic Analysis of the Treatment Regimens of Patients Having Cardiovascular Diseases with Drugs of the Antithrombotic Action - Nemchenko, A. S. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of our study is to conduct the pharmacoeconomic analysis of the treatment regimens of patients having cardiovascular diseases (CVDs) with antithrombotic drugs, namely clopidogrel and acetylsalicylic acid, in Ukraine. Materials and Methods: The results of a randomized, blind Clopidogrel versus Aspirin in Patients at Risk of Ischemic Event study (clopidogrel, n = 9599 and acetylsalicylic acid, n = 9588) and materials of unified clinical protocols in the specialty â€œCardiologyâ€ and data of the â€œAvailable medicinesâ€ reimbursement program in Ukraine were used in the work. Results and Discussion: Based on available clinical studies of the effectiveness of using drugs with the antithrombotic action in patients with CVD, the direct and indirect costs for further analysis of the total cost of the disease were calculated. It was found that the direct cost of the treatment with clopidogrel was 2.16 times higher than the cost of the treatment with acetylsalicylic acid. The total cost of the treatment of one patient with clopidogrel was 20.35% higher than with acetylsalicylic acid. The analysis by the â€œcost-effectivenessâ€ method showed that the cost-effectiveness ratio (CER) for acetylsalicylic acid was 13837.33 UAH/529.76 USD and for clopidogrel was 17366.66 UAH/664.88 USD. The cost of an incremental CER additional unit per one saved life when treating with clopidogrel is 5788.71 UAH/221.62 USD. Conclusion: Summing up the results of the study conducted, it has been found that the therapy with clopidogrel is more expensive; however, this drug is included in the reimbursement program in Ukraine, and therefore, the state partially compensates the patient for the expenses of it. Despite the fact that the therapy with acetylsalicylic acid should be carried out on a permanent basis in patients with CVD, it is necessary to include it in the â€œAvailable medicinesâ€ reimbursement program. The inclusion of drugs with acetylsalicylic acid in the list of reimbursed drugs will improve the health of patients with CVD and will help to save public funds that may be lost due to disability of the patient.